Дерево на крыше: [сборник] / Виктория Токарева - Токарева Виктория Самойловна (АСТ, 2009)
Экземпляры: ф. 1 (20101206) / Инвентарный номер: 96820 / Цена: 175.01 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 51 / ББК: 84(2Рос=Рус)6